PERBEDAAN MODEL PEMBELAJARAN TWO STAY TWO STRAY DENGAN MODEL PEMBELAJARAN INDEX CARD MATCH TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS - Hairun Nisah; Amin Harahap (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
This study aims to identify whether there is a significant difference between the Two stay two stray model and the Index card match model on students' mathematical communication abilities. The pretest-posttest design for the comparison group uses a purposive sampling method because the sampling is adjusted to the material to be taught. Participants in this study were class VIII students of SMP Muhammadiyah 25 Rantau Prapat. A group of students from class VIII A and class VIII B at the Muhammadiyah 25 Rantau Prapat private school were used as the research sample. The research instrument used is a valid description test. From the results of the hypothesis analysis it was found that Ho was accepted and H1 was rejected so that there was no difference in the average results of students' mathematics learning. So it can be concluded that the Index Card Match and Two Stay Two Stray cooperative learning models can improve students' mathematical communication abilities.